Tour Guides' Intercultural Communication Strategies In Toraja - Arny Irhani Asmin (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2022)
This study presents Torajanese tour guides’ strategies in intercultural communication based on four dimensions, they are knowledge, communication skills, traits and interpersonal relationship. The result of this study revealed that tour guides in Tana Toraja, South Sulawesi handled conflicts or conflicts that may be encountered in intercultural communication according to the competencies they have learned and experience in the field. The majority of respondents said that English proficiency, friendliness and broad understanding of tourist attractions are important points in their work. Thus, by understanding this, communication problems that may occur can always be resolved properly.